Analisis Penerapan Manajemen Sumber Daya Manusia dalam Meningkatkan Kinerja Pegawai di Era Digital pada Kantor Komisi Pemilihan Umum Kabupaten Nias Utara (Jurnal Riset Manajemen dan Akuntansi, 2025)
This research is based on a problem that occurred in the North Nias Regency KPU, namely the implementation of human resource management which is still not good, such as resistance to change, the need for continuous training and adjustment to new work systems, high work pressure on some employees due to inappropriate employee placement and division of work and work systems that involve applications make it difficult for employees to follow, resulting in a lack of employee work effectiveness. This study uses qualitative methods to determine the implementation of human resource management, obstacles, and strategies to improve employee work effectiveness. Based on the results of interviews with all predetermined informants using a list of questions prepared by the North Nias Regency KPU, it can be concluded that the implementation of human resources has not been fully implemented to improve work effectiveness even though it has been planned and systematic. This is caused by limited facilities and infrastructure such as slow internet access and other technological devices directly related to work and budget limitations resulting from budget efficiency from the Central Government. Strategies that can be implemented to improve the effectiveness of employee performance through the implementation of human resource management in the digital era at the North Nias Regency General Election Commission include preparing thorough and scheduled plans, implementing risk mitigation, implementing the formation of teams that can work together for efficient completion of a task, carrying out evaluations for improvements so that obstacles that have occurred do not recur and involving employees in planning and decision making. The results of this study recommend improving facilities and infrastructure, as well as appropriate work planning and placement, to reduce work stress and enable employees to adapt quickly to the work environment.